Investment Contracts for Agriculture : Maximizing Gains and Minimizing Risks - World Bank (Washington, DC, 2015)
Private investment in agriculture in developing countries, both domestic and foreign, has been on the rise for nearly two decades. This paper focuses on large-scale agricultural projects in developing countries, involving the lease of farmland, which rose sharply after the food crisis of 2008. It is important that such investments are sustainable not only in the long term, but also beneficial in the short term with minimal risks or negative effects. This paper looks at one approach to achieving this namely, carefully devised contracts with investors, and in doing so offers a number of concrete solutions. This paper marries two substantial bodies of research to show how investment contracts can be set up to promote sustainable development. The paper presents the top five positive outcomes and the five downsides from private sector investments in large scale agricultural projects. This is derived from empirical evidence gathered by the United Nations Conference on Trade and Development (UNCTAD) and the World Bank after visiting large-scale agricultural projects (UNCTAD and World Bank 2014). The paper then proposes legal options to maximizing the main positive outcomes and minimizing the main downsides through better drafting of contracts between investors and governments for the lease of farmland. This derived from work conducted by the International Institute for Sustainable Development (IISD), which studied almost 80 contracts and produced a guide to negotiating contracts for farmland and water, including a model contract.